Implementasi Kebijakan Dana Bantuan Operasional Sekolah Di Sekolah Dasar Inpres Lelejae Kecamatan Bulu Taba Kabupaten Pasangkayu - Irmayanti, Ike; Nasrullah; Rachmad (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2025)
This study aims to determine the implementation of the School Operational Assistance (BOS) Fund Policy at Inpres Lelejae Elementary School using a descriptive qualitative research method. The types of data used are primary and secondary data, with data collection techniques carried out through observation, interviews, and documentation. The number of informants totaled seven people, and data analysis was conducted using the Miles, Huberman, and Saldana model. This study applies the theory of George C. Edward III, which includes four indicators: communication, resources, disposition, and bureaucratic structure. Based on the research results, the implementation of the School Operational Assistance (BOS) fund policy has been running fairly well. This is evident from the application of George Edward III’s theory through the following aspects: (1) Communication established by the school principal is clear and effective regarding BOS fund information at Inpres Lelejae Elementary School. (2) Resources available at the school are adequate and capable of managing the BOS funds. properly in accordance with applicable procedures, although not all school facilities have been improved using BOS funds. (3) Disposition functions effectively, as seen in the cooperation between the principal, teachers, and the BOS fund management team. (4) Bureaucratic structure runs well, as evidenced by the commitment to establishing cooperation in accordance with the BOS technical guidelines.